Screening and HPLC methods for carotenoids in sweetpotato, cassava and maize for plant breeding trials - Kimura, Mieko; Kobori, Cintia N.; Rodriguez-Amaya, Delia B.; Nestel, Penelope (Elsevier B.V., 2007)
Analytical methods for sweetpotato, cassava and maize were developed. In orange and salmon-fleshed sweetpotatoes, (all-E)-beta-carotene predominated and results of spectrophotometric screening and HPLC quantification did not differ significantly. In yellow-fleshed sweetpotato and cassava, however, spectrophotometric screening overestimated the HPLC values because of the presence of several minor carotenoids. Aside from (all-E)-beta-carotene, Z-isomers were present in cassava in appreciable amounts. For both crops, extraction with acetone or tetrahydrofuran: methanol. (1: 1), using a mortar and pestle or a Polytron homogenizer, gave equivalent results. Rehydration of dry maize at room temperature for 30 min or at 85 degrees C for 5, 10 or 15 min gave equivalent results. Concentrations obtained with the C18 and C30 columns did not differ significantly for zeaxanthin, lutein, beta-cryptoxanthin and beta-carotene in the all-E-configuration, but their Z-isomers were difficult to locate in the chromatogram obtained with the C30 column. Extraction with tetrahydrofuran:methanol (1:1) gave significantly lower results for zeaxanthin and lutein. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: sweetpotato; cassava; maize; analysis; carotenoids; provitamin A